INTERPRETATION (TA'WIL) AMONG QUR’ANIC EXEGETES BETWEEN SHAR??AH GUIDELINES AND METHODOLOGICAL DEVIATIONS: AN ANALYTICAL STUDY IN THE LIGHT OF THE SCIENCES OF THE QUR’AN AND ?AD?TH - Zahra Ali; Almughera Abdulmunm Najm Al Lami (STAI Al-Hamidiyah Bangkalan, 2025)
This study examines the concept of interpretation (ta?w?l) among Qur’anic exegetes, focusing on the balance between Shar??ah-based guidelines and methodological deviations that have emerged in exegetical traditions over time. The research aims to clarify the proper scholarly understanding of ta?w?l and to identify its legitimate boundaries as established by the disciplines of Qur’anic and ?ad?th studies. Through an analytical and critical approach, the study highlights the methodological foundations adopted by authoritative exegetes while also exposing forms of interpretive deviation that result from neglecting linguistic principles, contextual coherence, and authentic prophetic traditions. By employing the tools of the sciences of the Qur’an and ?ad?th, the research evaluates various interpretive approaches and demonstrates the impact of methodological adherence—or lack thereof—on the soundness of exegetical understanding. The study concludes that valid ta?w?l must conform to Arabic linguistic rules, the objectives of Islamic law (maq??id al-shar??ah), and authentic Sunnah, whereas deviation from these principles leads to intellectual and methodological distortions in the interpretation of Islamic texts. Keywords:, , , , .